(untitled) (Research, Society and Development, 2022)
Plant-derived molluscicides have been indicated as selective and low-cost strategies for the control of Biomphalaria glabrata (Say, 1818), an intermediate host of schistosomes. This study aimed to evaluate the aqueous and ethanolic extracts of leaves of plants present in the Cerrado such as Caryocar brasiliense Camb., Ximenia americana L., Piptadenia viridiflora (Kunth) Benth., and Schinopsis brasiliensis Engl. as alternatives in the control of the mollusk B. glabrata. For this, leaves were collected from plants at the in Montes Claros-MG. Extracts at concentrations of 150, 100, 75, 50, and 25 μg/mL, a positive control containing niclosamide at 3 μg/mL, and a negative control containing dechlorinated water were used to verify the molluscicidal activity. To evaluate toxicity to non-target organisms, Artemia salina was treated with extract concentrations of 10, 100, and 1000 μg/mL. The tested aqueous and ethanolic extracts showed significant mortality within 24 h of exposure. At concentrations above 75 μg/mL, the aqueous extracts of P. viridiflora, C. brasiliense, and S. brasiliensis achieved mortality higher than 90%. Regarding ethanolic extracts, mortality above 80% was observed for all tested plants at concentrations above 50 μg/mL. No toxicity was observed against A. salina. Thus, high molluscicidal activity of ethanolic and aqueous extracts of the tested plants against adult B. glabrata was observed and no toxicity was observed against A. salina.